Accuracy of Gasometry in Electrolyte Evaluation: What is the difference between the gasometry and the laboratory in the measurement of electrolytes? - Sousa, Francisco José de; Cochito Sousa, Sofia; Vaz, Sara; Abecasis, Francisco (Journal of the Portuguese Society of Anesthesiology, 2021)
Background: The measurement of sodium, potassium and chloride is widely used in clinical practice. It can be done through a serum or gasometric sample. The ease of blood collection and the fast availability of results would make gasometry the ideal method. However, the literature data on the accuracy of gasometry are not consensual, thus, the current method of choice is the serum sample. We intended to compare the accuracy of sodium, potassium and chloride measurement between the gasometry and the serum ionogram. Methods: Prospective observational study of children aged 28 days to 17 years who underwent elective surgery at a Pediatric Surgery Service during one year. During the perioperative period, 3 laboratory evaluations were performed with ionogram analysis in a serum sample and gasometry and their results were compared. Results: 65 children with a median age of 10 years (IQR 3.6-15), 77% male. 161 determinations of sodium, 154 of potassium and 143 of chloride were obtained. There was a mean difference in sodium, potassium and chloride values between the two methods of: 1±1.89 mmol/L, 0.3±0.19mmol/L and -5±1.81 mmol/L (p <0.001). There was a strong correlation between sodium (r=0.64) and chloride (r=0.78) and very strong with potassium (r=0.9). It was possible to establish a linear regression and obtain a correction factor between the two methods. Conclusions: There was a strong correlation between the two methods, therefore, both can be used in clinical practice. A correction factor can be applied to the gasometry’s potassium and chloride results.